Educational Migration as a Tool for Increasing the Labor Force - Tamara K. Rostovskaya; Leysan A. Davletshina (National Research Mordova State University, 2024)
Introduction. The decrease in the population of Russia in recent decades has been caused by ongoing natural decline and decrease in migration growth. The government's policy of increasing the country's migration attractiveness has not yet produced the expected results. The average version of the population forecast indicates a decrease in the number, an increase in the proportion of the population older than the able-bodied, a decrease in the proportion of the population younger than the able-bodied, which will subsequently be reflected in the size of the workforce. The purpose of the study is to analyze the current parameters of the labor force; to study educational migration as a source of attracting foreign graduates to work in Russia. Materials and Methods. The paper examines the current parameters of the Russian labor force, and draws conclusions on changes in key labor market indicators. The current regulations and legal acts regulating labor migration have been identified, including those on attracting highly qualified specialists and retaining graduates from foreign countries to work in Russia. Results. As a result of the study of the state policy in the field of education, measures have been identified to expand the accessibility of the educational services market in Russia for foreign students. Possible options for their further employment in Russian companies and for work abroad are presented. The state policy of the main donor countries of foreign students in Russia, as well as government regulation measures in Kazakhstan, Tajikistan, Turkmenistan and Uzbekistan, has been studied. Discussion and Conclusion. The results of this study can be used in the process of developing state migration and educational policy, in the field of improving the legislative regulation of educational migration and the subsequent attraction of foreign graduates to employment in Russia.